Singapore: AgroConnect.com - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
AgroConnect.com is a B2B agricultural exchange offering an online e-trading platform for agricultural products, services and ideas.